(untitled) (Journal of the College of Basic Education, 2026)
Mongolian women in the Golden Horde of Fayhaq society enjoyed their full rights. They played a major role in peacemaking decisions , as well as their a ctive participation in most of the sultanh’s decisions. They even assumed the throne at certain times from behind the scenes , and intervened in the decision to install the sultans . They often nominated their sons for power in a greement with the Mongol Princes. The queens also owned a lot of Private Property , contributed to trade , and sponsored councils of scholars therein.